Learning About Evaluation and Antifungal Activity of Simpur Leaf Extract Shampoo (Dillenia Indica L) Towards Candida Albicans Causes Dandruck - sidiq, fahmi; Fauzi, Hery (International Journal of Ethno-Sciences and Education Research, 2023)
Simpur leaf (Dillenia indica L) is a plant that contains polyphenolic compounds, flavonoids, steroids, terpenoids, tannins and saponins that function as antifungal agents. Candida albicans is a fungus that can cause skin candidiasis. The purpose of this study was to formulate simpur leaf extract into a shampoo dosage form by testing its antifungal activity. The shampoo preparations were made in 3 formulas with varying concentrations of 5%, 10% and 20% then an evaluation was carried out which showed the shampoo preparations had met the requirements such as organoleptic, homogeneity, pH, viscosity, foam height, stability and hedonic tests. The antifungal activity test used the well method with negative control without the addition of extract and 2% ketoconazole was used as a positive control. Tests of simpur leaf extract against the fungus Candida albicans showed a concentration of 20% had the largest inhibitory diameter of 11.55 mm compared to concentrations of 5% (6.398 mm) and 10% (8.375 mm). While the shampoo preparation test showed that F3 with a concentration of 20% had the largest inhibition zone diameter of 12.008 mm compared to F1 and F2 with a concentration of 10% (9.775%) and 5% (6.725 mm). The negative control had an inhibition zone of 2.13 mm and the positive control had an inhibition zone of 13.78 mm.